Konseling realitas untuk mereduksi stres pada orangtua tunggal - Hanif Kartika Indrasari (Procedia : Studi Kasus dan Intervensi Psikologi, 2021)
The client is a 57 years old woman with complaints of feeling disappointed, irritable, palpitations, chest pain, sweating for no reason that interferes with daily activities. The results of the medical examination did not show any physiological problems. Based on the assessments carried out through interviews, observation, graphic tests, Depression Anxiety Stress Scale (DASS) and WHODAS indicate that the client is experiencing stress. The intervention provided was six sessions of reality counseling. The results of the intervention showed a decrease in stress scores from 25 to 13 on the DASS scale and accompanied by changes in more productive behavior.